The Repression of Percy Jackson in the Lightning Thief Novel (2005) - Merry Rullyanti; Ice Inda Rukmana (UNIVED Press, 2014)
The purpose of this research are: (1) To analyze what are the repression of Percy Jackson, (2) To analyze what cause the repression of Percy Jackson, (3) To analyze how Percy Jackson overcome his repression.this research uses theory by Jacques Lacan namely the imaginary and the symbolic, this research uses the descriptive qualitative method because it does not use research data such as number. The result of this research are: (1) the repression of Percy Jackson is divided into two kinds of the imaginary and the symbolic, where in the imaginary Percy Jackson has repression from the past that made him depression and in symbolic Percy Jackson have repression from what he saw and he heard is a symbol from monster and gods, Percy was depression when he experiencing it. (2) The cause of repression of Percy Jackson because he is as son of Poseidon (god of sea), that should not be allowed to have children of human. (3) Percy Jackson against the repression of him, he returns the stolen lightning bolt from Zeus and thwart World War III. Keywords: The Lightning Thief, repression, the imaginary, the symbolic.